2020
DOI: 10.1002/anie.202009128
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Total Synthesis of Euphoranginol C, Euphoranginone D, ent‐Trachyloban‐3β‐ol, ent‐Trachyloban‐3‐one, Excoecarin E, and ent‐16α‐Hydroxy‐atisane‐3‐one

Abstract: A divergent synthetic approach to biogenetically related diterpenoids such as ent-kauranes, ent-trachylobanes, ent-beyerane, and ent-atisane has been developed. The unified synthetic route involves the De Mayo reaction to rapidly generate the bicyclo[3.2.1]-octane moiety of ent-kaurane. The key reactions also include bioinspired nucleophilic cyclopropanation generating the [3.2.1.0 2,7 ]-tricyclic core of ent-trachylobane and regioselective cyclopropane fragmentation furnishing ent-beyerane and ent-atisane thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 103 publications
0
6
0
1
Order By: Relevance
“…For the analogous all carbon variant (X=Y=C, Figure 1A), while cationic rearrangements are well established, [14] a limited number of radical triggered ring expansions are known [15] . The analogous nucleophilic opening is extremely rare [16] . However, when concentrating our focus on the heterocyclic variant where X=N, our searches found no known ring expansions.…”
Section: Introductionmentioning
confidence: 88%
“…For the analogous all carbon variant (X=Y=C, Figure 1A), while cationic rearrangements are well established, [14] a limited number of radical triggered ring expansions are known [15] . The analogous nucleophilic opening is extremely rare [16] . However, when concentrating our focus on the heterocyclic variant where X=N, our searches found no known ring expansions.…”
Section: Introductionmentioning
confidence: 88%
“…Seit ihrer Entdeckung wurde diese Transformation in zahlreichen Totalsynthesen angewandt, was ihr großes synthetisches Potenzial hervorhebt. [5,6,11] Voraussetzung für diesen Reaktionsweg ist die Erzeugung des 1,2-Diradikals durch direkte Anregung des Enol-tautomers. Daher sind die klassische De-Mayo-Reaktion [10] und ihre formalen synthetischen Äquivalente [12] in der Regel auf solche Substrate beschränkt, bei denen das Enol-Tautomer überwiegend in Lösung vorliegt, da die Anregung des Keto-Tautomers zu seinem n-π*-Triplett-Zustand die gewünschte Cycloaddition verhindert und zu unerwünschter Nebenreaktivität führen kann.…”
Section: Introductionunclassified
“…The structure of 7 was unambiguously determined through X-ray analysis. [14] Better yield was obtained later by using 0.6 equivalents 1n HCl (aq) after stirring for 5 h. This procedure may serve as an example of nucleophilic displacement in the formation of cyclopropanes. Moving forward, reduction of the highly sterically hindered C11 ketone was achieved under drastic Wolff-Kishner conditions by stirring at 210 8C for 50 h. Using the same procedure described above, pentacyclic trachylobanes ent- To access ent-beyerane and ent-atisane, we explored the regioselective cyclopropane fragmentation of trachylobane (Scheme 3 B).…”
mentioning
confidence: 96%
“…Eventually, we found that BF 3 •2 AcOH [13] gave ent-kaurene-type 14 and ent-phyllocladene-type [2e] 15 in a one pot reaction, and the structures were unambiguously confirmed by X-ray analysis. [14] It is noteworthy that the treatment of intermediate 14' with BF 3 •2 AcOH resulted in its C9 epimerization via an oxonium intermediate. In parallel, the De Mayo reaction was attempted on substrate epi-9, affording C9-epi-kaurane-type 16 as the single isomer.…”
mentioning
confidence: 99%